SASTRA REMAJA (TEENLIT) SEBAGAI MEDIA ALTERNATIF DALAM MENINGKATKAN BUDAYA LITERASI - Ninawati Syahrul (Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract. The presence of adolescent literature - known as teenlit- is a necessity so loved by the teenagers. As one of the literary genres, teenlit seems to be not too complicated. In addition to the story plot that is easy to trace, the style of language is